A study on the usage of silicone in extrusion-based 3D printing technique - Teo, Guo Hua (Nanyang Technological University, 2022)
The demand for 3D printed silicone parts have been increased throughout the years in many industries such as built environment, aerospace engineering, electronics and biomedical. The 3D silicone printing techniques and application offers many advantages in manufacturing of silicone parts and composites, including their ability to manufacture parts that are relatively low in cost and high in precision and that they can be created in low-volume production. Every day, there will be research on new silicone printers being created or upgraded to print different class of materials, and this Final Year Project aims to study the usage of silicone as the main form of material in extrusion-based 3D printing techniques. Silicone material flow rate between different grade of silicone in room temperature and with presence of ice-cube (assume to be 0 degree) will also be discussed in this paper. Printing of concentric shaped silicone cubes will be tested out using a 3D modified printer set-up and printhead throughout the whole experiment as well as using it to find out the optimization of printing parameters such as temperatures, print speed, viscosity, and pump speeds.